COMPORTAMENTO GLICÊMICO EM PROTOCOLO EXPERIMENTAL DE SEPSE1 - Centenaro, Ana Luíza Holzcshuh; Sulzbacher, Maicon Machado; Salamoni, Bethânia; Goettems, Pauline Brendler; Heck, Thiago Gomes; Ludwig, Mirna Stela (Salão do Conhecimento, 2013)
Resumo